2006
DOI: 10.1007/s00262-006-0235-6
|View full text |Cite
|
Sign up to set email alerts
|

Individual Vγ2-Jγ1.2+ T cells respond to both isopentenyl pyrophosphate and Daudi cell stimulation: generating tumor effectors with low molecular weight phosphoantigens

Abstract: Human Vγ2Vδ2 T cells exhibit T cell receptor-dependent, MHC-unrestricted recognition of antigen and play important roles in tumor and pathogen immunity. To characterize antigen recognition by the Vγ2Vδ2 TCR, we used the combined approach of spectratyping and CDR3 sequence analysis that measures changes in the TCR repertoire before and after stimulation with a phosphoantigen (isopentenyl pyrophosphate) or an irradiated tumor cell line (Daudi B lymphoma). Here we describe common Vγ2 chains that are substantially… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
48
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(51 citation statements)
references
References 42 publications
3
48
0
Order By: Relevance
“…This idea is relevant to the improvement of mAb-based cancer immunotherapy where a combination of mAbs specific to tumor Ag(s) with CD137 cross-linking induces direct NK cell-mediated tumor lysis. Specifically, our findings suggest that combination of Ab-based cancer immunotherapies with either adoptive transfer of in vitro expanded ␥␦ T lymphocytes or systemic injection of ␥␦ T-lymphocyte stimulating agents (zoledronic acid) [8][9][10] may improve clinical outcome through the enhancement of direct and ADDC tumor killing by NK cells.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…This idea is relevant to the improvement of mAb-based cancer immunotherapy where a combination of mAbs specific to tumor Ag(s) with CD137 cross-linking induces direct NK cell-mediated tumor lysis. Specifically, our findings suggest that combination of Ab-based cancer immunotherapies with either adoptive transfer of in vitro expanded ␥␦ T lymphocytes or systemic injection of ␥␦ T-lymphocyte stimulating agents (zoledronic acid) [8][9][10] may improve clinical outcome through the enhancement of direct and ADDC tumor killing by NK cells.…”
Section: Discussionmentioning
confidence: 89%
“…7 Approximately 70% of ␥␦ T lymphocytes express the V␥2V␦2 TCR and can be expanded and activated by phosphoantigens such as the cholesterol biosynthesis intermediate, isopentenylpyrophosphate (IPP), or synthetic bisphosphonates (eg, pamidronate disodium and zoledronic acid). [8][9][10] Upon stimulation, ␥␦ T lymphocytes acquire the capacity to destroy solid tumors of diverse origins such as squamous cell carcinoma of the head and neck (SCCHN), melanoma, colon cancer, and breast carcinoma, 4,[11][12][13] suggesting that ␥␦ T lymphocytes are important antitumor effector cells. The validity of this antitumor function is further supported by mouse models demonstrating that mice deficient in ␥␦ T cells have increased sensitivity to the development of methylcholanthrene (MCA)-induced tumors.…”
Section: Introductionmentioning
confidence: 99%
“…However, we showed that the response relies primarily on public Vγ2 chain sequences that exist at high frequency within the starting repertoire of BCG-naïve macaques. These same public Vγ2 chains, positively selected during normal ontogeny, encode the response to other Vγ2Vδ2 T cell antigens including alkylphosphates or tumor cells 49 , and are not specific for mycobacteria. The response to BCG is either the result of cross-recognition, where the mycobacterium mimics an antigen encountered previously, or the Vγ2Vδ2 T cell receptor recognizing a host antigen that is modulated or modified during BCG infection.…”
Section: Discussionmentioning
confidence: 99%
“…ZA has also been shown to play a role in activation of γδ T cells in an antigen-dependent manner [10]. Furthermore, treatment with ZA and interleukin-2 (IL-2) results in increased serum levels of TRAIL in patients with prostate cancer [11].…”
Section: Introductionmentioning
confidence: 99%
“…Zoledronic acid (ZA) is a bisphosphonate that is used to prevent the loss of bone mass and to lower the risk of skeletal complication in patients with bone metastasis [9]. ZA has also been shown to play a role in activation of γδ T cells in an antigen-dependent manner [10]. Furthermore, treatment with ZA and interleukin-2 (IL-2) results in increased serum levels of TRAIL in patients with prostate cancer [11].…”
mentioning
confidence: 99%